RESILIENT SYSTEMS: PLANNING AND IMPLEMENTING DISASTER RECOVERY SOLUTIONS - Gudimetla, Sandeep Reddy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
This paper explores the critical elements of resilient systems, focusing on the planning and implementation of disaster recovery solutions. It highlights the significance of resilience in maintaining system operations during and after adverse events such as cyber-attacks and natural disasters. The comprehensive framework presented covers risk assessment, business impact analysis, and recovery strategy development, emphasizing the importance of proactive planning. Various implementation strategies, including redundant systems, data backup protocols, and cloud-based solutions, are examined. Practical insights are provided through case studies from different industries, demonstrating successful disaster recovery implementations. The paper also addresses the challenges faced in disaster recovery planning, such as budget constraints and technological limitations, and discusses future trends like the integration of artificial intelligence and machine learning in enhancing disaster recovery processes. By providing a thorough understanding of the planning and execution of disaster recovery solutions, this paper serves as a valuable resource for practitioners aiming to ensure system resilience in the face of disruptions.